2014
DOI: 10.1002/aoc.3100
|View full text |Cite
|
Sign up to set email alerts
|

Hiyama cross‐coupling reaction catalyzed by a palladium salt of 1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride under microwave irradiation

Abstract: An efficient catalytic system using 1-benzyl-4-aza-1-azoniabicyclo[2.2.2]octane chloride ((BeDABCO) 2 Pd 2 Cl 6 ) was developed for the Hiyama cross-coupling reaction of various aryl halides with triethoxy(phenyl)silane. The substituted biaryls were produced in excellent yields in short reaction times using a catalytic amount of this catalyst in NMP at 100°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In continuation of our recent investigations on the synthesis and applications of the palladium complex of 1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride with palladium chloride ((BeDABCO) 2 Pd 2 Cl 6 ), we now report the extension of this complex as an efficient and highly active homogeneous catalyst for the cross‐coupling reaction of various acyl chlorides with phenylboronic acid under phosphine‐free conditions (Scheme ).…”
Section: Resultsmentioning
confidence: 91%
“…In continuation of our recent investigations on the synthesis and applications of the palladium complex of 1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride with palladium chloride ((BeDABCO) 2 Pd 2 Cl 6 ), we now report the extension of this complex as an efficient and highly active homogeneous catalyst for the cross‐coupling reaction of various acyl chlorides with phenylboronic acid under phosphine‐free conditions (Scheme ).…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, good yields were achieved with chloroarens bearing electron-donating or electron-withdrawing substituents in short reaction time under microwave heating (Scheme 50) [107]. The same authors have revealed another protocol for Hiyama reaction of just about the same substrate scope, using palladium salt of 1-benzyl-4-aza-1azoniabicyclo-[2.2.2]octane chloride and KF as an activator under microwave irradiation [108]. 1-Methyl-2-aminoalkylimidazole derivative was reported as an efficient ligand for Hiyama reaction under solvent-free conditions in the presence of Pd(OAc)2.…”
Section: Hiyama Cross-coupling Reactionmentioning
confidence: 99%
“…The ionic complex 21 was very efficient for the coupling of aryl halides ( 5 , Hal = Cl, Br, I) and the trimethoxysilane 9 in the presence of CsF to afford the corresponding coupling products with excellent results (68‐98%) 29…”
Section: Arylation Reactionsmentioning
confidence: 99%